PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING START WITH A QUESTION TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 20 PADANG - Ravi Mach Hendra (Jurnal Edukasi dan Penelitian Matematika, 2020)
Mathematical communication skills of students of class VIII SMP Negeri 20 Padang are still low. This is because the learning process has not been optimal to improve students' mathematical communication skills. One effort that can be made to improve students' mathematical communication skills is by implementing an active learning strategy type Learning Start with a Question. (LSQ). The purpose of this study is to describe and analyze whether the mathematical communication skills of students who learn using the active learning strategy type Learning Start with a Question are better than the mathematical communication skills of students who learn using conventional learning.Keywords — Learning Start With a Question, Mathematical Comunication Skill